A recombinant canine distemper virus expressing interleukin-7 enhances humoral immunity. (15th March 2019) - Chen, Chen; Zhou, Ming; Yan, Xiao-geng; Chen, Yi-xi; Cui, Min; Chen, Huan-chun; Fu, Zhen-fang; Zhao, Ling
Abstract : Canine distemper (CD) causes gastrointestinal and respiratory and/or neurological signs and results in high morbidity and mortality, remaining a threat to carnivores around the world. Live-attenuated vaccines have been widely used to reduce the number of CD outbreaks, but efforts are still needed to improve immune efficiency. Interleukin-7 (IL-7) has been reported to boost host immunity by recruiting follicle helper T (TFH ) or germinal center (GC) B cells. Here, we constructed a recombinant canine distemper virus (rCDV) by reverse genetics and evaluated the properties of six intergenic sites for insertion of a foreign gene. We found that the P/M intergenic region was the optimal site to insert a foreign gene into the CDV genome. The effect of overexpressing IL-7 on rCDV immunogenicity was then evaluated in a mouse model. We found that mice immunized with rCDV-IL7 could not significantly enhance the maturation of dendritic cells (DCs) but significantly facilitated the generation of TFH cells, GC B cells and plasma cells (PCs), as well as the formation of GCs, consequently enhancing the production of CDV-specific neutralizing antibodies and total IgG. Together, these results suggested that the overexpression of IL-7 by rCDV could enhance humoral responses by activating the TFH –GC B–PC axis, which will help to improve vaccines for CD.